The Correlation between Teachers’ Educational Background and Students’ Achievement: A Study at Private Islamic Junior High Schools in Jambi - Shynta Amalia; Loviana Rizqa; Muhammad Iqbal Ramdhani (Universitas Islam Negeri (UIN) Sulthan Thaha Saifuddin Jambi, 2021)
Although the demand for mastering English is getting higher, the student’s achievement fell short of expectation. Several empirical studies indicated that one of the sources of the students’ lack in English achievement was the teachers’ qualification. There had been schools that let the teachers with non-English Education backgrounds teach English at schools. As the researchers concerned this phenomenon, this study aimed to seek the relationship between the teachers’ educational background and the students’ English learning achievement. The research design was a correlation study. The sample of the study was chosen purposively. The samples were chosen from 3 Private Islamic junior high schools in Jambi city Indonesia with A accreditation status. 244 eighth graders and 4 English teachers participated in this study. The data were collected by using a questionnaire and unobtrusive measures of the students’ English achievement. The result of the coefficient correlation between teachers’ educational background and students’ achievement was r=0.032. It means that those variables were positively correlated. However, r=0.032 was considered low correlation. This study hopefully contributes to the school. It’s important that the principals or policy maker of schools facilitate all teachers’ activities which contribute to the development of their professionalism.